2003
DOI: 10.1105/tpc.009845
|View full text |Cite
|
Sign up to set email alerts
|

ARC1 Is an E3 Ubiquitin Ligase and Promotes the Ubiquitination of Proteins during the Rejection of Self-Incompatible Brassica Pollen

Abstract: ARC1 is a novel U-box protein required in the Brassica pistil for the rejection of self-incompatible pollen; it functions downstream of the S receptor kinase (SRK). Here, we show that ARC1 has E3 ubiquitin ligase activity and contains several motifs that influence its subcellular localization. ARC1 can shuttle between the nucleus, cytosol, and proteasome/COP9 signalosome (CSN) when expressed in tobacco BY-2 suspension-cultured cells. However, ARC1 localization to the proteasome/ CSN occurs only in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
299
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 323 publications
(309 citation statements)
references
References 63 publications
2
299
0
8
Order By: Relevance
“…As discussed earlier, the U-box-containing proteins are newly identified E3 ubiquitin ligases that are present in yeast, plants, animals, and humans [35,62,63]. However, the number of U-box proteins varies among different organisms with a larger number of such proteins existing in the plant genomes.…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%
“…As discussed earlier, the U-box-containing proteins are newly identified E3 ubiquitin ligases that are present in yeast, plants, animals, and humans [35,62,63]. However, the number of U-box proteins varies among different organisms with a larger number of such proteins existing in the plant genomes.…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%
“…We have previously shown that transient coexpression of Brassica SRK 910 with Brassica ARC1 in tobacco BY-2 cells resulted in relocalization of Brassica ARC1 from the cytosol/nucleus to endoplasmic reticulum (ER)-associated proteasomes (Stone et al, 2003;Fig. 3, M and S).…”
Section: The Effect Of Active Kinases On the Subcellular Localizationmentioning
confidence: 99%
“…The end result of this pathway is pollen rejection by preventing compatible pollen responses such as pollen grain hydration and pollen tube penetration into the stigma (described under compatible pollinations; Dickinson 1995 ). Following SCR/SP11 binding to SRK, the SRK-MLPK complex is proposed to recruit the ARM repeat-containing 1 (ARC1 ) E3-ubiquitin ligase (Stone et al 2003 ;Samuel et al 2008 ). B. napus ARC1 was the fi rst downstream signaling component identifi ed for SRK and was shown to be required for the rejection of self-pollen (Gu et al 1998 ;Stone et al 1999 ).…”
Section: Self-incompatibility In the Genus Arabidopsismentioning
confidence: 99%
“…Following from this, the role of ARC1 in the self-incompatibility pathway was proposed to promote the ubiquitination and degradation of the proposed compatibility factors by the 26S proteasome (Stone et al 2003 ). Through an ARC1-interaction screen, Exo70A1 was identifi ed as a candidate compatibility factor targeted by ARC1 (Samuel et al 2009 ).…”
Section: Self-incompatibility In the Genus Arabidopsismentioning
confidence: 99%